KARTUN KARIKATUR MEDIA KOMUNIKASI SOSIAL DALAM MEDIA CETAK - Sri Indratmi Yudiarti (Institut Seni Indonesia Surakarta, 2012)
Caricature Cartoon, a whole word that can be realized in the picture. Pictures like this are usually found in the print media, newspapers, magazines and books. Some of the readers sometimes only a cursory look, if by chance they are definitely worth high humor laugh. And became interested to look at the message conveyed by the cartoon. In plain cartoon caricature does further highlight the value of humor, even if the message is a sad event. All sorts of events in the life of society; economics, politics and culture that is sad and happy is an object of interest to the caricaturist. Creative and emotional sensitivity is a challenge for the caricaturist, as they should be able to create an image of humor without any individuals, groups or institutions that offended and angry. Caricatures cartoon have always painted face figure distorted by the message object. So the face looks funny, still included the character or characteristics belong to the relevant figures. Through the approach of Communication Science, Psychology and Sociology gained Caricature Cartoon explanation that contributes role as media of social communication. Observations were made at random to caricature cartoons published in Jawa Pos Suara Merdeka and Kompas newspaper,. Thirdly the paper gives special place caricature cartoon images on the page that contains the public opinion. On these pages loaded freelance writing (essay), letters to the editor, opinion editor of the paper for a particular event. Conclusion of this observation is the existence of a caricature cartoon, that he was able to become the media of social communication, as an interpersonal communication media, broadcast media, and media storage. Cartoon caricatures are able to make the reader receives messages of social communication wise and high-minded, laughing even laugh at himself. Key words : Cartoon caricature, media, social communications